The Study of “Desire” and “Becoming‌ Woman” in Yerma Through Deleuze and Guattari's Views - Zahra Taheri (زن در فرهنگ و هنر, 2022)
This article focuses on the notion of “desire” in Yerma (1934), by Federico Garcia Lorca, the famous Spanish writer and dramatist. Yerma is one of the dramas in Lorca’s ‘rural trilogy’. Adopting the perspective of left thinkers and using Gilles Deluze and Fleix Guattari’s views on psychoanalysis, the writer discusses how the notion of “desire” through a deleuzian perspective is not associated with loss but power and can, thus, end up in change and “becoming.” To elaborate this process, the study has deployed a descriptive-analytic method to the text, and it has focused on the notions of ‘paranoid desire,’ ‘schizoid desire’ and ‘becoming woman.’ It is argued that Yerma, as a prototype of minority figures, is subjected to those strategies of ‘otherization’ which she cannot help tolerating due to an internalization of the family and social discourses of norms and stereotypes, which is still true to the lives of many women even these days. Yerma finds no way out of such stagnant life scripts but through a sudden outrageous rebellion against the system (and its representative—Juan). Such rebellion questions the dominant paranoid control exerted by every hierarchical system in society. These challenges pursue a type of “deterritorialization” of such systems and their meta-narratives by opening new horizons which introduce new types of relationships and orders which are far different from the mainstream culture and, thus, chaalenging, unsettling, and dangerous. In fact, they are new voices which can be heard.